Exploitation history, status, and sustainability challenges of sea cucumber fisheries in the Sapuka Islands, Indonesia (Wallacea) - RATNAWATI GATTA; ANDI NUR APUNG MASSISENG; AWALUDDIN AWALUDDIN; SUTRA NOBU; JAYA JAYA; SRI ENDAH PURNAMANINGTYAS (Society for Indonesian Biodiversity, 2025)
Abstract. Gatta R, Massiseng ANA, Awaluddin, Nobu S, Jaya, Purnamaningtyas SE. 2025. Exploitation history, status, and sustainability challenges of sea cucumber fisheries in the Sapuka Islands, Indonesia (Wallacea). Biodiversitas 26: 2565-2575. The Sapuka Archipelago, Indonesia, located within the Wallacea Region, is known for its rich marine biodiversity, particularly its diverse sea cucumber populations. These echinoderms are highly valued in international markets due to their significant economic and export potential. However, increasing global demand has raised concerns regarding overexploitation and long-term sustainability. This study examines the historical development and current condition of sea cucumber fisheries in the region. Evidence suggests that intensive and continuous harvesting has led to notable declines in the populations of commercially valuable species. Data were obtained from fisher logbooks, focus group discussions with local communities, and trade network records. Historically, fishing practices evolved from shallow-water collection using ladung in the 1960s-1970s to deeper-water harvesting employing scuba gear from the 1980s onward. Of the 19 species currently recorded, 11 are considered high value, with six listed under CITES Appendix II. Most captured individuals fall within the 18-30 cm length range and weigh between 300-600 grams, indicating selective targeting of reproductively mature specimens. Both fishers' observations and historical data confirm a decline in species richness, from 30 to 19 species, and in annual production, from over 1,000 tons to under 100 tons within two decades. The need for sustainable management is urgent and should be a top priority for all of us to prevent further depletion. Export values are influenced by species, quality (moisture and condition), size, production volume, and the Rupiah-US Dollar exchange rate. Primary export markets include Singapore, Hong Kong, South Korea, and Malaysia.